Determinasi terhadap Nilai Perusahaan (Studi Emperis Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia) - Syahdina, Aang; Qanitah, Audi Nafisa; Suwandi, Danisha Nazwasabilla; Ramadhan, Eka Gilang; Fhatia, Freethy Libra; Situmorang, Sarah Angelica Puan (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
This study was conducted to analyze the impact of Current Ratio, Return on Assets, and Debt to Equity Ratio on Firm Value in the banking sector listed on the Indonesia Stock Exchange during the period of 2020-2024. Secondary data collection involved 27 banking companies selected from a total of 46 companies using purposive sampling technique. The analytical method employed was panel data regression with the assistance of Eviews 10 software. Classical assumption testing was performed through normality test, multicollinearity test, and heteroscedasticity test. Meanwhile, hypothesis testing was conducted using t-test to examine partial effects, F-test to examine simultaneous effects, and Adjusted R² coefficient of determination. The research findings indicate that Current Ratio does not exert a significant influence on Firm Value. Return on Assets demonstrates a negative but insignificant effect on Firm Value, whereas Debt to Equity Ratio shows a positive yet insignificant effect on Firm Value. When examined collectively, these three independent variables do not exhibit a significant influence on Firm Value.